Obstetrical Anal Sphincter Injuries and the Need for Adequate Care. Issue 2 (March 2019) - Elliot, Victoria; Yaskina, Maryna; Schulz, Jane
Abstract : Background: An estimated 4% to 6.6% of women delivering vaginally sustain obstetrical anal sphincter injuries (OASI). Despite this, a gap exists in the provision of postpartum care to women globally. Given the negative impact of OASI, action is needed, and multidisciplinary perineal clinics can help. Consequently, such a clinic was established in 2011 at the Royal Alexandra Hospital (RAH), a tertiary care center in Edmonton, Alberta. Objective: This study assesses the state of perineal clinics specializing in OASI internationally and locally by investigating the literature for descriptions of specialized perineal clinics for women with OASI, describing the RAH perineal clinic, and assessing the prevalence of OASI at the RAH in the context of the clinic. Methods: A search of peer-reviewed literature was conducted on Medline and observations and interviews of RAH perineal clinic staff were conducted, as was a medical chart review. Results: Articles describing only 10 perineal clinics specializing in OASI were found, with varying structures. The multidisciplinary RAH clinic, like one other clinic, has a strong physiotherapy focus, with education and Pilates classes and one-on-one appointments offered by pelvic floor physiotherapists. In 2016, of the 326 (6.9%) vaginal deliveries that resulted in OASI at the RAH, only 66.0% (215) were referred to the clinic. Conclusions: Multidisciplinary perineal clinics are needed globally. Despite the creation of the perineal clinic at the RAH, women continue to lack specialized care after OASI. It is crucial that healthcare professionals specializing in OASI share their experiences to establish best practices and create new, and improve existing, perineal clinics.